آراء الشيخ محمد بن صالح العثيمين في أشهر المعاملات المالية المعاصرة - بن منصور, خير الدين; بكار, محفوظ (University of Eloued-جامعة الوادي, 2022)
"هذه الدراسة اشتملت على بيان آراء الشيخ محمد بن صالح العُثَيْمين –رحمه الله- في عدة قضايا مالية معاصرة، يحتاجها كل مسلم في معاملاته المالية. وقد بيَّنَّا صورة كل مسألة بدقة. وقبل ذلك عرَّفْنا بفقه المعاملات المالية المعاصرة، وذكرنا أهم خصائصه، ومنهج التصدي له. كما وضعنا سيرة مختصرة للشيخ ابن عثيمين. وقد خرجنا بعدة نتائج أهمها: أن الأصل عند الشيخ ابن عُثيمين في المعاملات المالية المعاصرة هو الحلُّ والإباحة، فلا يُحرّم منها إلا ما دل الدليل على حرمته.""This study included a statement of the views of Sheikh Mohammed bin Saleh Al-Othaymeen - may god have mercy on him- on several contemporary financial issues, which every Muslim needs in his financial transactions. We have outlined the picture of each issue thoroughly. Before that, we were introduced to the jurisprudence of contemporary financial transactions, and we mentioned its most important characteristics, and the approach to address it. We have also compiled or put a brief biography of Shaykh Ibn Othaymeen. We have come up with several conclusions, the most important of which are: that the origin of Shaykh Ibn Othaymeen in contemporary financial transactions is permissibility, which is not deprived of them unless evidence indicates its inviolability."
مذكرة ماستر
Keywords: آراء، الشيخ محمد بن صالح العثيمين، المعاملات المالية المعاصرة.; The views, Sheikh Mohammed bin Saleh Al-Othaymeen, contemporary financial issues.